Injectable hydroxyapatite filler and preparation method thereof
By using animal-derived bone and pore-generating agent modified hydroxyapatite, combined with aminolated polyethylene glycol-guar prepolymer and collagen, the mechanical properties and biocompatibility of hydroxyapatite are difficult to balance. The problem has achieved the application prospects in the field of medical beauty.
Patent Information
- Application Number
- CN202411137486.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-08-19
AI Technical Summary
Hydroxyapatite has high brittleness, difficult to match bone tissue, and poor binding effect with organic materials, making it difficult to balance mechanical properties and biocompatibility, limiting its application in the field of medical beauty.
Animal-derived bones are used as the source of hydroxyapatite, and their pore structure is improved by modification of pore-generating agents, combining amino-polymers of polyethylene glycol-guar gum and collagen to form porous structures, enhancing mechanical properties and biological Compatibility.
It improves the mechanical properties and biocompatibility of hydroxyapatite, enhances its binding ability with bone tissue, and meets the safety and effects of osteoinduction and medical beauty filling.
Smart Images

Figure CN119236167A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of biomaterials, and in particular to an injectable hydroxyapatite filler and a preparation method thereof. Background Art
[0002] Hydroxyapatite is one of the best filling material options and can be used in the medical beauty industry. The chemical composition of hydroxyapatite (HA) is similar to the minerals of human bone tissue, can be chemically bonded with natural bone, and has good biological properties.
[0003] The disadvantages of hydroxyapatite are its high brittleness and difficulty in matching its mechanical properties with bone tissue. The current improvement route is to compound hydroxyapatite with organic materials in order to achieve complementary performance advantages. However, in actual applications, it was found that the combination of hydroxyapatite and organic materials was poor, and it was difficult to balance the mechanical properties and biocompatibility of hydroxyapatite, which hindered its further application. Summary of the invention
[0004] In order to improve the mechanical properties and biocompatibility of hydroxyapatite, the present application provides an injectable hydroxyapatite filler and a preparation method thereof.
[0005] In the first aspect, the present application provides a method for preparing an injectable hydroxyapatite filler using the following technical solution: A method for preparing an injectable hydroxyapatite filler comprises the following steps: Animal-derived bones are calcined and crushed to obtain natural hydroxyapatite; Natural hydroxyapatite and a porogen are mixed and stirred in a thickening liquid to form a hydroxyapatite slurry, the hydroxyapatite slurry is spray-dried into particles to obtain hydroxyapatite microspheres, the particle size of the hydroxyapatite microspheres is 20-60 μm, and then the hydroxyapatite microspheres are calcined to obtain porous hydroxyapatite; Dispersing porous hydroxyapatite in a first organic solvent, adding an epoxysilane coupling agent, heating for reaction, and filtering to obtain epoxidized hydroxyapatite; Dissolving polyethylene glycol and guar gum in water, adjusting the pH to acidic, adding an aldehyde cross-linking agent, heating for reaction, and filtering to obtain a polyethylene glycol-guar gum prepolymer; Dispersing the polyethylene glycol-guar gum prepolymer in a second organic solvent, adding an aminosilane coupling agent, heating for reaction, and filtering to obtain an amino polyethylene glycol-guar gum prepolymer; The epoxidized hydroxyapatite, the amino polyethylene glycol-guar gum prepolymer and the collagen aqueous solution are mixed and shaken to obtain an injectable hydroxyapatite filler.
[0006] By adopting the above technical solution, compared with artificially synthesized hydroxyapatite, animal-derived bone is used as the source of hydroxyapatite, which has higher biological activity and safety and is suitable for the fields of bone tissue regeneration and medical aesthetic filling.
[0007] Natural hydroxyapatite is modified by a porogen to improve the degree of the pore structure inside the natural hydroxyapatite and increase the specific surface area of the natural hydroxyapatite, so as to promote the amino polyethylene glycol-guar gum prepolymer and collagen to fully bind to the hydroxyapatite; the amino polyethylene glycol-guar gum prepolymer has good biocompatibility, and collagen is one of the components of bone tissue. Both of them have a strong binding ability with hydroxyapatite, which plays a role in improving the mechanical properties and bone induction ability of hydroxyapatite while meeting the safety requirements.
[0008] After epoxidation, hydroxyapatite can further chemically bond with amino polyethylene glycol-guar gum prepolymer and collagen aqueous solution through the reaction between epoxy groups and amino groups, forming a stable structure without cross-linking, thereby further improving the compressive resistance of hydroxyapatite fillers.
[0009] Optionally, in the step of preparing the polyethylene glycol-guar gum prepolymer, the weight ratio of polyethylene glycol, guar gum and aldehyde cross-linking agent is 1:(1.2~1.5):(0.2~0.35).
[0010] By adopting the above technical scheme, the input amounts of polyethylene glycol and guar gum are controlled, and the degree of cross-linking of the prepolymer is controlled, so that the polyethylene glycol-guar gum prepolymer can not only undergo subsequent amino modification, but also adhere to and bind on the surface of hydroxyapatite, thereby improving the mechanical properties and biocompatibility of the hydroxyapatite filler.
[0011] Optionally, the molecular weight of the polyethylene glycol is 400-1000, and the molecular weight of the guar gum is 75000-90000.
[0012] By adopting the above technical solution, polyethylene glycol and guar gum with lower molecular weight make the prepolymer more tough and easier to spread on the surface of hydroxyapatite, thereby promoting the improvement of the mechanical properties of hydroxyapatite.
[0013] Optionally, in the step of preparing an injectable hydroxyapatite filler, the weight ratio of the epoxidized hydroxyapatite, the amino polyethylene glycol-guar gum prepolymer and the collagen aqueous solution is 1:(0.5~1):(6~8), and the molecular weight of the collagen in the collagen aqueous solution is 20000~30000Da, and the concentration is 5~10wt%.
[0014] By adopting the above technical solution, the molecular weight and concentration of collagen are controlled, so that epoxidized hydroxyapatite and amino polyethylene glycol-guar gum prepolymer can be fully dispersed and combined with collagen to obtain an injectable hydroxyapatite filler with good stability.
[0015] Optionally, the method for preparing the porogen comprises the following steps: The polyvinyl alcohol, emulsifier and water are mixed and stirred, the pH is adjusted to acidic, and formaldehyde solution is added dropwise at the same time. After the addition is completed, the mixture is heated for reaction. After the reaction is completed, the mixture is filtered and washed to obtain polyvinyl alcohol microspheres. The polyvinyl alcohol microspheres are dispersed in water, acrylic acid, an initiator and concentrated sulfuric acid are added in sequence, heated for reaction, and filtered and washed after the reaction is completed to obtain a porogen.
[0016] By adopting the above technical scheme, the polyvinyl alcohol microspheres modified by acrylic acid grafting can fully contact the surface of natural hydroxyapatite, improve the surface and internal morphology of hydroxyapatite, form interconnected channels, and promote the combination of hydroxyapatite with amino polyethylene glycol-guar gum prepolymer and collagen, thereby improving the toughness of the hydroxyapatite filler while ensuring safety.
[0017] Optionally, the weight ratio of the polyvinyl alcohol, emulsifier and formaldehyde is 1:(0.5~0.7):(0.15~0.25); the weight ratio of the polyvinyl alcohol microspheres, acrylic acid, initiator and concentrated sulfuric acid is 1:(0.3~0.4):(0.02~0.05):(0.08~0.12).
[0018] By adopting the above technical solution, the shape of the porogen microspheres is controlled and the porogenic effect on natural hydroxyapatite is improved.
[0019] Optionally, the thickening liquid is prepared by mixing sodium carboxymethyl cellulose, glycerol and water in a weight ratio of 1:(0.3-0.6):(15-20).
[0020] By adopting the above technical solution, hydroxypropyl methylcellulose makes the thickening liquid have a certain viscosity, promotes the adhesion of the porogen to the surface of natural hydroxyapatite, and then forms pores under high-temperature calcination.
[0021] Optionally, in the step of preparing porous hydroxyapatite, the weight ratio of the natural hydroxyapatite, the porogen and the thickening liquid is 1:(0.3-0.45):(3-5).
[0022] Optionally, in the step of preparing epoxidized hydroxyapatite, the weight ratio of the porous hydroxyapatite to the epoxysilane coupling agent is 1:(0.08~0.15); in the step of preparing the amino polyethylene glycol-guar gum prepolymer, the weight ratio of the polyethylene glycol-guar gum prepolymer to the aminosilane coupling agent is 1:(0.15~0.25).
[0023] In a second aspect, the present application provides an injectable hydroxyapatite filler, which is prepared based on the above preparation method.
[0024] In summary, this application has the following beneficial effects: 1. The present application modifies natural hydroxyapatite by a porogen, improves the degree of pore structure inside natural hydroxyapatite, increases the specific surface area of natural hydroxyapatite, and promotes the amino polyethylene glycol-guar gum prepolymer and collagen solution to fully combine with hydroxyapatite; the amino polyethylene glycol-guar gum prepolymer has good biocompatibility, and collagen is one of the components of bone tissue. Both of them form a strong binding ability with hydroxyapatite, which plays a role in improving the mechanical properties and bone induction ability of hydroxyapatite while meeting safety requirements. After epoxidation, hydroxyapatite can be further chemically bonded with the amino polyethylene glycol-guar gum prepolymer and the collagen aqueous solution through the reaction of epoxy groups and amino groups, and a stable structure can be formed without cross-linking, further improving the compressive strength of the hydroxyapatite filler.
[0025] 2. The porogen of the present application is polyvinyl alcohol microspheres modified by acrylic acid grafting. The porogen can fully contact the surface of natural hydroxyapatite, improve the surface and internal morphology of hydroxyapatite, form interconnected pores, and promote the combination of hydroxyapatite with amino polyethylene glycol-guar gum prepolymer and collagen, thereby improving the toughness of the hydroxyapatite filler while ensuring safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM picture of the hydroxyapatite filler prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0027] The present application is described in further detail below.
[0028] Preparation Example 1 The preparation method of the porogen comprises the following steps: Weigh 1000 g of polyvinyl alcohol, 500 g of emulsifier, 8 L of water, and 375 g of formaldehyde solution.
[0029] The molecular weight of polyvinyl alcohol is 35000, the emulsifier is Span-80, and the concentration of formaldehyde solution is 40wt%.
[0030] Polyvinyl alcohol, emulsifier and water were mixed and stirred, sulfuric acid solution was added to adjust the pH of the reaction system to 3.5, and then formaldehyde solution was added dropwise. After the addition was completed, the mixture was heated to 65°C and reacted for 2 hours. After the reaction was completed, the mixture was filtered and washed with water to obtain polyvinyl alcohol microspheres.
[0031] Weigh 500 g of polyvinyl alcohol microspheres, 5 L of water, 150 g of acrylic acid, 10 g of initiator, and 40 g of concentrated sulfuric acid.
[0032] The initiator is ammonium cerium sulfate, and the concentration of concentrated sulfuric acid is 98wt%.
[0033] Polyvinyl alcohol microspheres were dispersed in water, acrylic acid, initiator and concentrated sulfuric acid were added in sequence, heated to 50°C, reacted for 3 hours, filtered and washed with water after the reaction was completed, and a porogen was obtained.
[0034] Preparation Example 2 The preparation method of the porogen comprises the following steps: Weigh 1000 g of polyvinyl alcohol, 700 g of emulsifier, 9 L of water, and 625 g of formaldehyde solution.
[0035] The molecular weight of polyvinyl alcohol is 35000, the emulsifier is Span-80, and the concentration of formaldehyde solution is 40wt%.
[0036] Polyvinyl alcohol, emulsifier and water were mixed and stirred, sulfuric acid solution was added to adjust the pH of the reaction system to 3.5, and then formaldehyde solution was added dropwise. After the addition was completed, the mixture was heated to 65°C and reacted for 2 hours. After the reaction was completed, the mixture was filtered and washed with water to obtain polyvinyl alcohol microspheres.
[0037] Weigh 500 g of polyvinyl alcohol microspheres, 5 L of water, 200 g of acrylic acid, 25 g of initiator, and 60 g of concentrated sulfuric acid.
[0038] The initiator is ammonium cerium sulfate, and the concentration of concentrated sulfuric acid is 98wt%.
[0039] Polyvinyl alcohol microspheres were dispersed in water, acrylic acid, initiator and concentrated sulfuric acid were added in sequence, heated to 50°C, reacted for 3 hours, filtered and washed with water after the reaction was completed, and a porogen was obtained.
[0040] Preparation Example 3 The difference between this preparation example and preparation example 1 is that polyvinyl alcohol microspheres are not grafted with acrylic acid, that is, polyvinyl alcohol microspheres are used as porogens.
[0041] Example 1 A method for preparing an injectable hydroxyapatite filler comprises the following steps: Animal-derived bones, specifically sheep bones, are taken, calcined at 950° C. for 2 h, and crushed to obtain natural hydroxyapatite.
[0042] Take a thickening liquid prepared from sodium carboxymethyl cellulose with a degree of polymerization of 500, glycerol and water in a weight ratio of 1:0.3:15.
[0043] Take 500 g of natural hydroxyapatite, 150 g of the porogen of Preparation Example 1, and 1500 g of thickening liquid, mix and stir, and soak for 1 hour to form a hydroxyapatite slurry. The hydroxyapatite slurry is spray-dried into particles at a spray temperature of 200°C to obtain hydroxyapatite microspheres with a particle size of 20~60 μm. Then the hydroxyapatite microspheres are calcined at 1100°C for 3 hours to obtain porous hydroxyapatite.
[0044] Take 100 g of porous hydroxyapatite and disperse it in 1 L of a first organic solvent, specifically a 95 wt% ethanol solution, add 8 g of an epoxy silane coupling agent, specifically γ-glycidyloxypropyltrimethoxysilane, heat to 60 ° C for reaction for 1.5 h, filter, wash with ethanol and water to obtain epoxidized hydroxyapatite.
[0045] Take 100 g of polyethylene glycol, 120 g of guar gum, and 20 g of aldehyde cross-linking agent.
[0046] The molecular weight of polyethylene glycol is 400, the molecular weight of guar gum is 75000, and the aldehyde cross-linking agent is specifically a 50wt% glutaraldehyde solution.
[0047] Dissolve polyethylene glycol and guar gum in 3 L of water, add phosphoric acid to adjust the pH to 5, add aldehyde cross-linking agent, heat to 85° C. and stir to react for 2 h, filter, and wash with water to obtain polyethylene glycol-guar gum prepolymer.
[0048] Take 100 g of polyethylene glycol-guar gum prepolymer and disperse it in 1 L of a second organic solvent, specifically toluene, add 15 g of an aminosilane coupling agent and 5 g of triethylamine, the aminosilane coupling agent is specifically 3-amino-trimethoxysilane, heat to 90 ° C and stir to react for 2 h, filter, wash with ethanol and water to obtain an amino polyethylene glycol-guar gum prepolymer.
[0049] Take 100 g of epoxidized hydroxyapatite, 50 g of amino polyethylene glycol-guar gum prepolymer, and 600 g of collagen aqueous solution.
[0050] The molecular weight of collagen in the collagen aqueous solution is 20000Da, and the concentration is 10wt%.
[0051] The epoxidized hydroxyapatite, the amino polyethylene glycol-guar gum prepolymer and the collagen aqueous solution were mixed and shaken for 3 hours to obtain an injectable hydroxyapatite filler, such as Figure 1 shown.
[0052] Example 2 A method for preparing an injectable hydroxyapatite filler comprises the following steps: Animal-derived bones, specifically sheep bones, are taken, calcined at 950° C. for 2 h, and crushed to obtain natural hydroxyapatite.
[0053] A thickening liquid is prepared by mixing sodium carboxymethyl cellulose with a degree of polymerization of 500, glycerol and water in a weight ratio of 1:0.6:20.
[0054] Take 500 g of natural hydroxyapatite, 225 g of the porogen of Preparation Example 2, and 2500 g of thickening liquid, mix and stir to form a hydroxyapatite slurry, spray dry the hydroxyapatite slurry into particles at a spray temperature of 200°C to obtain hydroxyapatite microspheres with a particle size of 20~60 μm, and then calcine the hydroxyapatite microspheres at 1100°C for 3 hours to obtain porous hydroxyapatite.
[0055] Take 100 g of porous hydroxyapatite and disperse it in 1 L of a first organic solvent, specifically a 95 wt% ethanol solution, add 15 g of an epoxy silane coupling agent, specifically γ-glycidyloxypropyltrimethoxysilane, heat to 60 ° C for reaction for 1.5 h, filter, wash with ethanol and water to obtain epoxidized hydroxyapatite.
[0056] Take 100 g of polyethylene glycol, 150 g of guar gum, and 35 g of aldehyde cross-linking agent.
[0057] The molecular weight of polyethylene glycol is 400, the molecular weight of guar gum is 75000, and the aldehyde cross-linking agent is specifically a 50wt% glutaraldehyde solution.
[0058] Dissolve polyethylene glycol and guar gum in 3 L of water, add phosphoric acid to adjust the pH to 5, add aldehyde cross-linking agent, heat to 85° C. and stir to react for 2 h, filter, and wash with water to obtain polyethylene glycol-guar gum prepolymer.
[0059] Take 100 g of polyethylene glycol-guar gum prepolymer and disperse it in 1 L of a second organic solvent, specifically toluene, add 25 g of an aminosilane coupling agent and 5 g of triethylamine, the aminosilane coupling agent is specifically 3-amino-trimethoxysilane, heat to 90 ° C and stir to react for 2 h, filter, wash with ethanol and water to obtain an amino polyethylene glycol-guar gum prepolymer.
[0060] Take 100 g of epoxidized hydroxyapatite, 10 g of amino polyethylene glycol-guar gum prepolymer, and 800 g of collagen aqueous solution.
[0061] The molecular weight of collagen in the collagen aqueous solution is 30000Da, and the concentration is 5wt%.
[0062] The epoxidized hydroxyapatite, the amino polyethylene glycol-guar gum prepolymer and the collagen aqueous solution were mixed and shaken for 3 hours to obtain an injectable hydroxyapatite filler.
[0063] Example 3 A preparation method of injectable hydroxyapatite filler The difference between this embodiment and embodiment 1 is that in the step of preparing porous hydroxyapatite, the porogen used in Preparation Example 3 is selected as the porogen.
[0064] Comparative Example 1 A method for preparing an injectable hydroxyapatite filler comprises the following steps: Animal-derived bones, specifically sheep bones, are taken, calcined at 950° C. for 2 h, and crushed to obtain natural hydroxyapatite.
[0065] 100 g of natural hydroxyapatite and 20 g of chitosan were mixed and stirred in a 2 wt% acetic acid aqueous solution for 4 h, and then 5 g of 50 wt% glutaraldehyde solution was added and stirring was continued for 4 h. The precipitate was filtered, washed with water and then dispersed in 0.01 M PBS buffer solution. The weight ratio of the precipitate to the PBS buffer solution was 1:10. After shaking, an injectable hydroxyapatite filler was obtained.
[0066] Comparative Example 2 A preparation method of injectable hydroxyapatite filler The difference between this comparative example and Example 1 is that the step of preparing porous hydroxyapatite is not provided, that is, natural hydroxyapatite is used to prepare epoxidized hydroxyapatite.
[0067] Comparative Example 3 A preparation method of injectable hydroxyapatite filler The difference between this comparative example and Example 1 is that in the step of preparing the polyethylene glycol-guar gum prepolymer, an equal amount of gelatin is used to replace the guar gum, and the molecular weight of the gelatin used is 75,000.
[0068] Comparative Example 4 A preparation method of injectable hydroxyapatite filler The difference between this comparative example and Example 1 is that in the step of preparing the polyethylene glycol-guar gum prepolymer, an equal amount of polyvinyl alcohol is used to replace the polyethylene glycol, and the molecular weight of the polyvinyl alcohol used is 35,000.
[0069] Comparative Example 5 A preparation method of injectable hydroxyapatite filler The difference between this comparative example and Example 1 is that the step of preparing the amino polyethylene glycol-guar gum prepolymer is not provided, that is, the injectable hydroxyapatite filler is prepared by using epoxidized hydroxyapatite, polyethylene glycol-guar gum prepolymer and hydrolyzed collagen solution.
[0070] Performance Testing The injectable hydroxyapatite filler was placed in a molding mold and freeze-dried at -60°C for 24 hours to obtain a test sample.
[0071] Mechanical property test: The test sample is a cylinder with a diameter of 8 mm and a height of 10 mm. The test sample is subjected to compression test using a universal mechanical testing machine. The test speed is 5 mm / min and the compression height ratio is 50%. The compressive strength of the injectable hydroxyapatite filler is measured.
[0072] The injectable hydroxyapatite filler was sterilized, and then immersed in a growth medium containing 10% bovine serum, 100 U / mL penicillin, and 100 U / mL streptomycin for 24 hours to obtain a hydroxyapatite extract.
[0073] Cell proliferation test: MC3T3-E1 cells were diluted to a cell concentration of 3.5×108 L -1 , 0.1 mL of cell suspension was taken out with a pipette and added to 4 6-well plates, each 6-well plate was divided into an experimental group and a control group, the control group added growth medium to the culture wells, and the experimental group added the hydroxyapatite extract prepared in each embodiment and comparative example, and cultured to the 3rd and 5th days. The corresponding culture wells were taken out, the original culture medium and extract were discarded, 100 μL of growth medium and 10 μL of CCK-8 reagent solution were added to each well, incubated in dark for 1 hour, and the absorbance value was read using an enzyme marker at a wavelength of 450 nm.
[0074] In the traditional hydroxyapatite compounding method, taking comparative example 1 as an example, the compressive strength of the hydroxyapatite filler is low, less than 2MPa, and its adaptability in the field of medical beauty filling is poor. However, the hydroxyapatite fillers of Examples 1 and 2 of the present application, by combining with amino polyethylene glycol-guar gum prepolymer and collagen aqueous solution, have a compressive strength close to 3MPa, and the mechanical properties are fully improved, with good application prospects.
[0075] Combining Comparative Examples 2 to 5 and Example 3, it can be seen that after hydroxyapatite is treated with a porogen, its binding ability with the amino polyethylene glycol-guar gum prepolymer and the collagen aqueous solution is improved, and after the polyvinyl alcohol microspheres in the porogen are grafted with polypropionic acid, the porous structure of hydroxyapatite is significantly improved. In addition, polyethylene glycol and guar gum can form a prepolymer that is well adapted to hydroxyapatite, and the binding ability of the prepolymer with hydroxyapatite is enhanced by amination.
[0076] The absorbance value of the experimental group was higher than that of the control group, indicating that the material has the effect of promoting osteoblast proliferation and has good biocompatibility, thereby stimulating bone induction and accelerating bone formation.
[0077] The absorbance values of the hydroxyapatite fillers of Examples 1 and 2 of the present application are significantly higher than that of the control group, thus showing a higher osteoblast proliferation ability. The absorbance value of Comparative Example 1, which is a representative traditional hydroxyapatite composite method, is not significantly increased compared with the absorbance value of the control group, and has poor biocompatibility.
[0078] Combining Comparative Examples 2 to 5 and Example 3, it can be seen that the biocompatibility of the hydroxyapatite filler can be greatly improved by treating with a porogen and combining with an amino polyethylene glycol-guar gum prepolymer.
[0079] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing an injectable hydroxyapatite filler, characterized in that: The following steps are involved: Animal-derived bones are calcined and crushed to obtain natural hydroxyapatite; Natural hydroxyapatite and a porogen are mixed and stirred in a thickening liquid to form a hydroxyapatite slurry, the hydroxyapatite slurry is spray-dried into particles to obtain hydroxyapatite microspheres, the particle size of the hydroxyapatite microspheres is 20-60 μm, and then the hydroxyapatite microspheres are calcined to obtain porous hydroxyapatite microspheres; Dispersing porous hydroxyapatite in a first organic solvent, adding an epoxysilane coupling agent, heating for reaction, and filtering to obtain epoxidized hydroxyapatite; Dissolving polyethylene glycol and guar gum in water, adjusting the pH to acidic, adding an aldehyde cross-linking agent, heating for reaction, and filtering to obtain a polyethylene glycol-guar gum prepolymer; Dispersing the polyethylene glycol-guar gum prepolymer in a second organic solvent, adding an aminosilane coupling agent, heating for reaction, and filtering to obtain an amino polyethylene glycol-guar gum prepolymer; The epoxidized hydroxyapatite, the amino polyethylene glycol-guar gum prepolymer and the collagen aqueous solution are mixed and shaken to obtain an injectable hydroxyapatite filler.
2. The method for preparing an injectable hydroxyapatite filler according to claim 1, characterized in that: In the step of preparing the polyethylene glycol-guar gum prepolymer, the weight ratio of polyethylene glycol, guar gum and aldehyde cross-linking agent is 1:(1.2-1.5):(0.2-0.35).
3. The method for preparing an injectable hydroxyapatite filler according to claim 2, characterized in that: The molecular weight of the polyethylene glycol is 400-1000, and the molecular weight of the guar gum is 75000-90000.
4. The method for preparing an injectable hydroxyapatite filler according to claim 1, characterized in that: In the step of preparing an injectable hydroxyapatite filler, the weight ratio of the epoxidized hydroxyapatite, the amino polyethylene glycol-guar gum prepolymer and the collagen aqueous solution is 1:(0.5~1):(6~8), and the molecular weight of the collagen in the collagen aqueous solution is 20000~30000Da, and the concentration is 5~10wt%.
5. The method for preparing an injectable hydroxyapatite filler according to claim 1, characterized in that: The preparation method of the porogen comprises the following steps: The polyvinyl alcohol, emulsifier and water are mixed and stirred, the pH is adjusted to acidic, and formaldehyde solution is added dropwise at the same time. After the addition is completed, the mixture is heated for reaction. After the reaction is completed, the mixture is filtered and washed to obtain polyvinyl alcohol microspheres. The polyvinyl alcohol microspheres are dispersed in water, acrylic acid, an initiator and concentrated sulfuric acid are added in sequence, heated for reaction, and filtered and washed after the reaction is completed to obtain a porogen.
6. The method for preparing an injectable hydroxyapatite filler according to claim 5, characterized in that: The weight ratio of the polyvinyl alcohol, emulsifier and formaldehyde is 1:(0.5-0.7):(0.15-0.25); the weight ratio of the polyvinyl alcohol microspheres, acrylic acid, initiator and concentrated sulfuric acid is 1:(0.3-0.4):(0.02-0.05):(0.08-0.12).
7. The method for preparing an injectable hydroxyapatite filler according to claim 1, characterized in that: The thickening liquid is prepared by mixing sodium carboxymethyl cellulose, glycerol and water in a weight ratio of 1:(0.3-0.6):(15-20).
8. The method for preparing an injectable hydroxyapatite filler according to claim 1, characterized in that: In the step of preparing porous hydroxyapatite, the weight ratio of the natural hydroxyapatite, the porogen and the thickening liquid is 1:(0.3-0.45):(3-5).
9. The method for preparing an injectable hydroxyapatite filler according to claim 1, characterized in that: In the step of preparing epoxidized hydroxyapatite, the weight ratio of the porous hydroxyapatite to the epoxysilane coupling agent is 1:(0.08-0.15); in the step of preparing the amino polyethylene glycol-guar gum prepolymer, the weight ratio of the polyethylene glycol-guar gum prepolymer to the aminosilane coupling agent is 1:(0.15-0.25).
10. An injectable hydroxyapatite filler, prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for preparing photo-curable bone repairing material from epoxy group-containing siloxane-clad modified hydroxyapatite
CN101966349A
Method for preparing porous bone repair scaffold with different magnesium phosphate phases based on 3D printing technology
CN110680953A
Preparation method of nano-hydroxyapatite and sulfonated polyether-ether-ketone composite material
CN112587732A
Anhydrous calcium phosphate bone cement and preparation method thereof
CN113769159A
Composite reinforced degradable material as well as preparation method and application thereof
CN116271263A